2019
DOI: 10.1158/1078-0432.ccr-19-0114
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral Adaptive Immunosuppression and Type 17 Immunity in Mismatch Repair Proficient Colorectal Tumors

Abstract: Purpose: Approximately 10% of patients with mismatch repair-proficient (MMRp) colorectal cancer showed clinical benefit to anti-PD-1 monotherapy (NCT01876511). We sought to identify biomarkers that delineate patients with immunoreactive colorectal cancer and to explore new combinatorial immunotherapy strategies that can impact MMRp colorectal cancer. Experimental Design: We compared the expression of 44 selected immune-related genes in the primary colon tumor of 19 patients with metastatic colorectal cancer (m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 28 publications
(42 reference statements)
0
44
0
Order By: Relevance
“… 28 As Coffelt et al 16 reported, IL-17 producing γδ T cells and neutrophils suppressed cytotoxic CD8 + T cells and promoted breast cancer metastasis; IL-17 is now being examined as a cause of tumor progression and resistance to therapy. It has been reported that IL-17 signature was associated with the resistance to anti-PD-1 therapy in colorectal cancer 29 and melanoma. 30 In this preclinical model, we identified CD4 + T cells and γδ T cells in the tumor produced IL-17.…”
Section: Discussionmentioning
confidence: 99%
“… 28 As Coffelt et al 16 reported, IL-17 producing γδ T cells and neutrophils suppressed cytotoxic CD8 + T cells and promoted breast cancer metastasis; IL-17 is now being examined as a cause of tumor progression and resistance to therapy. It has been reported that IL-17 signature was associated with the resistance to anti-PD-1 therapy in colorectal cancer 29 and melanoma. 30 In this preclinical model, we identified CD4 + T cells and γδ T cells in the tumor produced IL-17.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that the immune blocking effect of the tumor itself is great relative to generate immunosuppressive microenvironment. Llosa et al found that this immune function is caused by the upregulation of several checkpoint ligands, among which PD-1/PD-L1 is an important ligand[66]. The prognosis of early Endometrial Carcinoma (EC) is not correlated with MSI[67], but the results of EC in the middle and late stage were opposite.…”
mentioning
confidence: 99%
“…Notably, the γδT17 cells in human CRC also produced TNF, but were not cytotoxic. Given the observations that Th17-type immunity is detrimental in CRC [10,40], γδT17 cells may also contribute significantly to poor patient outcome [41,42]. Here, we show that TCRγδCD8 − T cells are indeed a major source of IL-17A and TNF in the tumors of APC Min/+ mice and that they represent an adequate model of human CRC also in this aspect.…”
Section: Discussionmentioning
confidence: 50%
“…Generally, this relatively short PD-1 antibody treatment did not affect immune responses or tumor growth in APC Min/+ mice. This may be caused by the pre-existing γδT17 cells response, as Th17-like responses were recently shown to limit the benefit of PD-1 antibody treatment in MSS CRC [40].…”
Section: Discussionmentioning
confidence: 99%